Six Sigma DMAIC for Shaking Stagnant Construction Cultures - A Conceptual Perspective - Ahmad A Mousa (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2015)
Cultural barrier is always perceived as the prime challenge for modernizing idle construction markets. Unsurprisingly, most changes in construction hinge on understanding the benefits of sustainable transformation. Persistent attempts in stagnant construction cultures have materialized in some noted changes. Successful sustainable transformation in such economies appears to be chiefly impeded at the execution level. The Kotter's model for change is globally accepted approach for comprehensive implementation of major business transformations. Modern organizational change initiatives typically embrace the notions of Six Sigma in a broader sense. This concept paper propose the use of Six Sigma DMAIC technique for reforming stagnant construction cultures. A case study from a challenged construction market is referred to for potential implication.